Gawain, Race, and the Borders in The Turke and Sir Gawain1. (3rd July 2022) - Otaño Gracia, Nahir I.
ABSTRACT: This essay works through ideas of settler colonialism, displacement, and border-crossings in order to investigate the character of Gawain. The Middle English Romance, The Turke and Sir Gawain ( TG ), seems to follow Gawain as he learns to be a better knight and to uphold ideologies of inclusivity, courtesy, and virtue which appear to invite and accept difference. Nevertheless, Gawain's attributes are also embedded in a borderland system in which Gawain, as a white borderland character, reinforces the status quo of the text in which Arthurian knights are the best knights and the Arthurian kingdom is expanded. The relation between and among "Gawain, " the "Turke, " and the "heathen soldan, " for example, serves to construct, deconstruct, and expand the borders of Arthur's kingdom by racializing, erasing, and violently destroying both the "Turke" and "Soldan." The Turke in particular is reborn as the Christian knight Sir Gromer.